2021
DOI: 10.1016/j.ijppaw.2021.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Host and geographic differences in prevalence and diversity of gastrointestinal helminths of foxes (Vulpes vulpes), coyotes (Canis latrans) and wolves (Canis lupus) in Québec, Canada

Abstract: Wild canids are hosts to a wide range of parasites and can play a role in transmission of zoonoses. As many parasites are transmitted through food webs, and wild canids are at high trophic levels, parasite prevalence and diversity in wild canids can serve as excellent indicators of ecosystem health. Our main objectives were to update knowledge on the composition of gastrointestinal helminths in wild canids from Québec, Canada, and to describe differences in parasite prevalence and diversity among canid species… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 71 publications
0
2
0
1
Order By: Relevance
“…Alternatively, there may be a spurious correlation due to habitat selection and resource partitioning. Epidemiological studies have shown that land cover may have a significant effect on the parasite prevalence of wild canids, with a pattern of increased prevalence of Taeniidae in grassland areas; this is thought to be secondary to the differences in intermediate hosts that are consumed by canids in each habitat type ( Bouchard et al, 2021 ; Watts et al, 2015 ). Culpeo foxes (native species) are usually associated with denser thicket or matorral vegetation, whereas chilla foxes (human-introduced species) usually show a preference towards open grasslands and scrublands in plains ( González del Solar & Rau, 2004 ; Jiménez & Novaro, 2004 ; Johnson & Franklin, 1994 ).…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, there may be a spurious correlation due to habitat selection and resource partitioning. Epidemiological studies have shown that land cover may have a significant effect on the parasite prevalence of wild canids, with a pattern of increased prevalence of Taeniidae in grassland areas; this is thought to be secondary to the differences in intermediate hosts that are consumed by canids in each habitat type ( Bouchard et al, 2021 ; Watts et al, 2015 ). Culpeo foxes (native species) are usually associated with denser thicket or matorral vegetation, whereas chilla foxes (human-introduced species) usually show a preference towards open grasslands and scrublands in plains ( González del Solar & Rau, 2004 ; Jiménez & Novaro, 2004 ; Johnson & Franklin, 1994 ).…”
Section: Discussionmentioning
confidence: 99%
“…Склад паразитофауни у популяціях лисиць часто змінюється і залежить від ряду факторів: ареалу, складу біоценозів, харчових зв'язків тощо, тому і є необхідність у його постійному моніторингу [2,3,6,11,12].…”
Section: вступunclassified
“…Collecting samples and studying intestinal parasite infections in carnivore hosts can be challenging. Samples are often obtained by trapping or hunting hosts and performing necropsies (e.g., [ 13 , 14 ]), which involves logistical and ethical considerations. These studies provide information about parasite presence and distribution, but do not provide longitudinal infection data within a host.…”
Section: Introductionmentioning
confidence: 99%